2016
DOI: 10.1007/s00453-016-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Rumor Spreading on Random Graphs

Abstract: We perform a thorough study of various characteristics of the asynchronous push-pull protocol for spreading a rumor on Erdős-Rényi random graphs G n,p , for any p > c ln(n)/n with c > 1. In particular, we provide a simple strategy for analyzing the asynchronous push-pull protocol on arbitrary graph topologies and apply this strategy to G n,p . We prove tight bounds of logarithmic order for the total time that is needed until the information has spread to all nodes. Surprisingly, the time required by the asynch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In [17] it was shown that, after appropriate normalization, the limiting distribution of the runtime of asynchronous pull on complete graphs converges and the limit is the sum of two independent Gumbel distributed random variables. Some more recent results on asynchronous rumor spreading are [15,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…In [17] it was shown that, after appropriate normalization, the limiting distribution of the runtime of asynchronous pull on complete graphs converges and the limit is the sum of two independent Gumbel distributed random variables. Some more recent results on asynchronous rumor spreading are [15,19,22].…”
Section: Introductionmentioning
confidence: 99%